Diagnostic value of calcaneal quantitative ultrasound in the evaluation of osteoporosis in middle-aged and elderly patients. Issue 2 (14th January 2022) - Li, Changzhou; Sun, Jifeng; Yu, Li
Abstract : Abstract: To study the correlation between calcaneal quantitative ultrasound (QUS) and dual-energy X-ray absorptiometry (DXA), and analyze the diagnostic value of calcaneal QUS in the evaluation of middle-aged and elderly osteoporosis. We assessed bone mineral density (BMD) at the femoral neck and intertrochanteric of left hip and lumbar spine (L1–L4) sites with DXA and QUS parameters of the right and left calcanei in a cohort of 82 patients over the age of 50 years. Using DXA parameters as the gold standard for the diagnosis of osteoporosis, the correlation coefficient between BMD and QUS parameters was calculated. Receiver operating characteristic curve was generated and areas under the curves were evaluated. Cut-off values for QUS were defined. In men, there was a moderate correlation between calcaneal QUS and proximal femoral BMD ( P  < .05), but no significant correlation between calcaneal QUS and lumbar BMD ( P  > .05). In women, calcaneal QUS were moderately correlated with lumbar spine and proximal femoral BMD ( P  < .05). Using DXA as the gold standard, the accuracy, sensitivity, specificity, positive predictive value, and negative predictive value of calcaneal QUS in the diagnosis of osteoporosis were 90.2%, 89.2%, 100%, 100%, and 50.0%, respectively. According to the receiver operating characteristic curve, when the QUS T-score of calcaneum was –1.8, the area under the curve was 0.888, the sensitivity was 73.21%, and the specificity was 92.31% ( P  < .05). When the QUS T-score of calcaneum was –2.35, the sensitivity was 37.2% and the specificity was 100%. Calcaneal QUS can be used to predict proximal femoral BMD in middle-aged and elderly people, as well as lumbar BMD in women. As a screening method for osteoporosis, calcaneal QUS has good specificity, so it can be recommended to use it as a pre-screening tool to reduce the number of DXA screening. When the QUS T-score of calcaneum is –1.8, it has the greatest diagnostic efficiency for osteoporosis; when the QUS T-score of calcaneum is ≤–2.35, it can be diagnosed as osteoporosis.